The Effectiveness of Using Make a Match Technique in Reading for Comprehension - Yusuf, Yusti Mutia; Saiful; Hamid, Sitti Maryam (FKIP Unismuh Makassar, 2025)
This study examined the use of the Make a Match Technique on literal reading comprehension. It was use descriptive text. Researcher was applied Pre- Experimental Research. It aimed at to find out the effectiveness of using Make a Match to improve the students’ reading comprehension at the second grade students’ of SMPN 1 Takalar 2022/2023. The sample of this research was the students of VIII. 1 class of SMPN 1 Takalar. This research was used purposive sampling technique. The researcher obtained the data using pre-test dan post-test. The mean score of the pre-test was 45,88 and post-test was 80,88. That was better increase of the mean score by students’ at the post-test. The test's outcome indicated a 3.273>2.036 significant difference between the t-test and t-table, indicating that the t-table was smaller than the t-test. That was proved by the t-table value 2.036 which was smaller than t-test 3.273. Based on the result of the analysis, it was concluded that using Make a Match technique could improved the students’ reading comprehension at the second grade students of SMPN 1 Takalar.